ENVIRONMENTAL LIFE CYCLE ASSESSMENT OF SMOKED FISH PRODUCTION: A CASE STUDY OF THE UNIVERSITY OF IBADAN FISH FARM (Journal of Engineering Studies and Research, 2025)
The study aimed to carry out a life cycle assessment (LCA) of the production and processing of smoked fish using the University of Ibadan Fish Farm as a case study to identify environmentally detrimental production and processing hotspots. The LCA used cradle-to-gate approach which involves the operations from breeding/hatching to the packaging of smoked fish. Four scenarios were drawn for assessing the impact by varying the energy and material resources. Six impact categories were measured for all four scenarios with Global Warming Potential (0.639 kg CO2-Eqiv.) having the highest impact while Human Toxicity Cancer Effect recorded the least impact (3.463e-11 CTUh). At the end of this LCA study, it was recommended that renewable energy sources as well as energy from bio-waste should be explored for the smoking kilns to achieve cleaner production.
Keywords: life cycle assessment, global warming, acidification potential, smog air, smoked fish production and processing